Balancing Notification Frequency and User Satisfaction in Task Management Tools - Paradeda, Raul; Silva, Euller Araújo da; Santos, Luiziane dos (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2025)
This study examines the role of customizable notification intervals in task management applications. Tarefácil, an app designed to send task reminders, was used as the study tool. Participants were divided into three groups, each assigned different notification intervals: 3 hours (C1), 5 hours (C2), or a choice between the two (C3). The results show that users highly value the ability to personalize notification intervals, even though fixed intervals did not negatively affect their experience. This research suggests future studies in contexts such as work and education, contributing to interaction design, psychology, and technology. The findings emphasize the importance of customization in improving user experience.